2021
DOI: 10.1002/adhm.202101190
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Hybrid Hydrogel Enhanced Antitumor Therapy through Multiple Destroying DNA Functions by a Triple‐Combination Synergistic Therapy

Abstract: Brachytherapy, as an effective setting for precise cancer therapy in clinic, can lead to serious DNA damage. However, its therapeutic efficacy is always limited by the DNA self‐repair property, tumor hypoxia‐associated radiation resistance as well as inhomogeneous distribution of the radioactive material. Herein, a multifunctional hybrid hydrogel (131I‐hydrogel/DOX/GNPs aggregates) is developed by loading gold nanoparticle aggregates (GNPs aggregates) and DOX into a radionuclide iodine‐131 (131I) labelled poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…ab15580 ) analysis were performed according to previous reports and imaged using an inverted fluorescence microscope (Leica, Germany). 51…”
Section: Methodsmentioning
confidence: 99%
“…ab15580 ) analysis were performed according to previous reports and imaged using an inverted fluorescence microscope (Leica, Germany). 51…”
Section: Methodsmentioning
confidence: 99%
“…Nonreactive dextran aldehyde crosslinks with dendrimer amines, lowering the free aldehyde content, preventing attachment to other organs, and forming the hydrogel's cohesive bulk. Researchers investigated how endogenous triggers alter the structure and characteristics of hydrogels in both in vitro and in vivo (Wang et al., 2021 ; Zhang et al., 2021 ). Additionally, research was also conducted regarding the possibility of using this structure as a nanoparticle depot for triggered cargo release (Deng et al., 2021 ; Li et al., 2022 ).…”
Section: Hydrogels For Localized Chemotherapy Of Liver Cancermentioning
confidence: 99%
“…Recent studies have demonstrated that hyperthermia induced by photothermal therapy (PTT) can prevent DNA self-repair and promote blood circulation to improve the hypoxic microenvironment, which can synergistically enhance the therapeutic efficacy of RT for cancer treatment. [15] However, the limited penetration depth of near-infrared (NIR) light may act as a barrier for photothermal activity and consequently restrict its clinical applications. Herein, the combinatorial treatment modality involving PTT and RT was able to compensate for the penetration depth of NIR and synergistically improve the therapeutic efficacy for tumor therapy.…”
Section: Introductionmentioning
confidence: 99%